Analysis of the Service Level of the Serang City Station During the Pandemic of COVID-19 - Arief Budiman; Rindu Twidi Bethary; Dwi Esti Intari; Syifa Kria Madani (Jurnal Fondasi, 2023)
The increasing number of COVID-19 cases in Indonesia has caused a decrease in the number of users of public transportation services, one of which is users of train transportation services. This makes some facilities at the station require adjustments to the applicable rules. The purpose of this study is to measure the level of satisfaction and importance of train station service during the COVID-19 pandemic, determine the gap between the level of satisfaction and importance, and determine the attributes that are prioritized for improvement. This research uses Service Quality and Importance Performance Analysis methods. The results of the data analysis show that the expected station services are not in accordance with what is received by users of Serang Station services. It is necessary to improve the quality of service and increase the number of facilities at the station to increase the satisfaction of service users who use Serang Station services.